IMPROVING SPEAKING SKILLS THROUGH SHADOWING TECHNIQUES (Modern education and development, 2025)
This article explores the effectiveness of shadowing techniques in improving speaking skills in language learners. Shadowing involves listening to a spoken model and simultaneously repeating it, which enhances pronunciation, fluency, and comprehension. Various studies support its positive impact on language acquisition. The methodology section details different shadowing techniques, while the discussion presents experimental findings. The results indicate that consistent practice with shadowing significantly improves oral proficiency.